Observable Reputation Trading - Hendrik Hakenes; Martin Peitz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
Is the reputation of a firm tradable when the change in ownership is observable? We consider a competitive market in which a share of owners must retire in each period. New owners bid for the firms that are for sale. Customers learn the owner's type, which reflects the quality of the good or service provided, through experience. After observing an ownership change they may want to switch firm. However, in equilibrium, good new owners buy from good old owners and retain high-value customers. Hence reputation is a tradable intangible asset, although ownership change is observable.
urn:nbn:de:bvb:19-epub-13420-2
Keywords: D40; D82; L14; L15; 330; Reputation; ownership change; intangible assets; theory of the firm